(untitled) (Fiep Bulletin - online, 2017)
The objective of this study is to present through a literature review, we raised about the practice ofResistance Training during pregnancy, with special focus on the benefits and effect on the health of the mother before, during andafter pregnancy. Data analysis was carried out through a literature textbook review of different periods and articles published inthe Scielo databases, the search was limited to periods or a year of works consulted for clarification on Physical Exercisessettings and gestation. In the face of considerations it is concluded that the practice of Physical Exercise is recommended, givingwomen physiological benefits pregnant women, psychological and social improvement of a healthy and balanced pregnancy andimproving the development of daily activities, whereas an exercise program physical for pregnant women is essential, and thatphysical education professionals emphasize targeted exercises for each pregnancy through periodic evaluations in order toreduce risks and develop health in pre- and post-pregnancy.